1996
DOI: 10.1901/jaba.1996.29-291
|View full text |Cite
|
Sign up to set email alerts
|

Training and Generalization of Affective Behavior Displayed by Youth With Autism

Abstract: The purpose of this study was to teach contextually appropriate affective behavior to 4 youths with autism. Treatment consisted of modeling, prompting, and reinforcement introduced in a multiple baseline design across response categories of affective behavior. During treatment, verbal praise and tokens were delivered contingent on appropriate affective responding during training trials. Modeling and verbal prompting were used as correction procedures. Each youth received treatment in either three or four respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
57
0
17

Year Published

1999
1999
2018
2018

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 79 publications
(78 citation statements)
references
References 18 publications
4
57
0
17
Order By: Relevance
“…The procedures resulted in the participants' use of contextually appropriate affective responses that generalized to untaught stimuli and settings. Gena, Couloura, and Kymissis (2005) extended upon and received similar results as Gena et al (1996) by teaching similar responses using similar procedures but also compared the use of in vivo and video modeling procedures as error correction procedures. The results from Gena et al (2005) suggested that both types of models were equally effective error-correction procedures to teach affective responses and might be able to be used interchangeably with individuals with ASD in these circumstances.…”
Section: Introductionmentioning
confidence: 82%
See 4 more Smart Citations
“…The procedures resulted in the participants' use of contextually appropriate affective responses that generalized to untaught stimuli and settings. Gena, Couloura, and Kymissis (2005) extended upon and received similar results as Gena et al (1996) by teaching similar responses using similar procedures but also compared the use of in vivo and video modeling procedures as error correction procedures. The results from Gena et al (2005) suggested that both types of models were equally effective error-correction procedures to teach affective responses and might be able to be used interchangeably with individuals with ASD in these circumstances.…”
Section: Introductionmentioning
confidence: 82%
“…The results suggest that individuals with ASD may be able to identify and discriminate between the necessary characteristics of affective stimuli. Consequently, reduced empathetic behavior by individuals with ASD may instead be due to untaught relations between affective stimuli and appropriate empathetic responses as has been suggested by Gena et al (1996).…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations